2022
DOI: 10.3390/met12071070
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of Plasma Electrolytic Oxidation Coatings on Ti-6Al-4V Eli Alloy Processed by Additive Manufacturing

Abstract: The additive manufacturing (AM) technique can produce Ti-6Al-4V ELI (extra low interstitial) alloy for personalized biomedical devices. However, the Ti-6Al-4V ELI alloy presents poor tribological behavior. Regarding this, coatings are a feasible approach to improve the wear resistance of this alloy. In the literature, the tribological behavior of TiO2 coatings incorporated with Ca and P formed by one-step plasma electrolytic oxidation (PEO) on Ti-6Al-4V ELI alloy processed by AM has not been investigated. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The coatings were able to exhibit high hardness and density, as well as high wear resistance. Santos et al [143] investigated a possible coating via the plasma electrolytic oxidation of Ti6Al4V for biomedical application and demonstrated improved wear resistance compared with the untreated samples. The post-treatment of Al-Si alloy via heat treatment and electric discharge alloying (EDA) was investigated in [144].…”
Section: Selective Laser Melting (Slm)mentioning
confidence: 99%
“…The coatings were able to exhibit high hardness and density, as well as high wear resistance. Santos et al [143] investigated a possible coating via the plasma electrolytic oxidation of Ti6Al4V for biomedical application and demonstrated improved wear resistance compared with the untreated samples. The post-treatment of Al-Si alloy via heat treatment and electric discharge alloying (EDA) was investigated in [144].…”
Section: Selective Laser Melting (Slm)mentioning
confidence: 99%
“…The aforementioned characteristics render titanium alloy highly promising in the domains of aerospace engineering, marine engineering, and biomedical engineering [6][7][8][9]. Furthermore, the utilization of titanium alloys as raw materials for additive manufacturing is highly commendable [10][11][12][13][14]. In the extensive application scenarios of titanium alloy, the service performance of titanium alloy is contingent upon its corrosion resistance [15], a critical property that has attracted considerable interest from researchers and engineers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, titanium alloys used as dental implants in the oral cavity are frequently exposed to fluoride ions from toothpaste Metals 2024, 14, 364 2 of 13 or tap water. It has been demonstrated that implants can often benefit from optimal surface roughness and microstructural features [14,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Anatase has been associated with superior cytocompatible behavior in terms of osteoblast proliferation and adhesion [16,17]. The rutile phase exhibits greater hardness compared to the anatase phase, along with reduced wear and friction properties [18][19][20]. By selecting the most optimal modes and combining components such as anatase and rutile, it is possible to improve the mechanical and tribological properties of the PEO coating.…”
Section: Introductionmentioning
confidence: 99%